Резонансная модель метеорного роя - Емельяненко, В.В. (Кинематика и физика небесных тел, 1990)
Рассмотрены особенности распределения частиц вдоль орбит метеорных роев при регулярном и стохастическом движении под действием возмущений от Юпитера. Построено двумерное отображение, в котором учитывается структура резонансов вида 1:j'. Это отображение использовано при статистическом моделировании функции распределения метеорных роев. Приведены примеры расчета распределений метеорных частиц для Персеид и Лирид. The peculiarities in the distribution of particles along the orbits of meteor streams for the regular and stochastic motion governed by perturbations from Jupiter are considered. The two-dimensional mapping taking into account the structure of 1:j' resonances is derived. This mapping is used for the statistical simulation of meteor streams. The examples of calculations of distribution functions for the Perseids and Lyrids arc given.